Customizable Diskless Solution for HPC Clusters - Ravera, Emanuel Mariano (2011)
Diskless clusters provide a stable, easily replicable and auto- deployable solution for High Performance Computing (HPC). On the other hand, the Intel® Cluster Ready program simplifies the selection, deployment, and management of HPC clusters by establishing a standard specification for them ensuring component and application interoperability. This work proposes to use a framework for on-the-fly creation of diskless solutions that allows users with little or no knowledge to create and deploy customized HPC clusters based on the Intel® Cluster Ready Specification.